2016
DOI: 10.3389/fphar.2015.00320
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol Ameliorates Ulcerative Colitis-Related Colorectal Cancer in Mice via Suppressing Inflammatory Responses and Epithelial-Mesenchymal Transition

Abstract: Celastrol, also named as tripterine, is a pharmacologically active ingredient extracted from the root of traditional Chinese herb Tripterygium wilfordii Hook F with potent anti-inflammatory and anti-tumor activities. In the present study, we investigated the effects of celastrol on ulcerative colitis-related colorectal cancer (UC-CRC) as well as CRC in vivo and in vitro and explored its underlying mechanisms. UC-CRC model was induced in C57BL/6 mice by administration of azoxymethane (AOM) and dextran sodium su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 50 publications
3
42
0
1
Order By: Relevance
“…It is a kind of triterpenoid extracted from the root of a traditional Chinese medicine called Tripterygium wilfordii . It was reported that celastrol could inhibit the development of IBD or colitis through several pathways, including: (1) regulating the oxidative stress and reducing lipid peroxide; (2) inhibiting the activation of the NLRP3 inflammasome; (3) increasing the levels of anti-inflammatory cytokines like IL-10; (4) enhancing the stability of intestinal epithelial barrier (152); (5) inhibiting the receptor interacting-protein 3/mixed lineage kinase domain-like protein-mediated programed necrosis pathway (153); and (6) inhibiting the production of NF-κB and its related inflammatory cytokines (154). Furthermore, it has been proven that celastrol can enhance the level of autophagy through the inhibition of the PI3K/Akt/mTOR signaling pathway in the colon tissue, and meanwhile reduce the production of several pro-inflammatory cytokines thus attenuating the inflammatory reaction in colon in IL-10-deficient mice (155).…”
Section: Pharmacological Intervention Of Autophagy In the Treatment Omentioning
confidence: 99%
“…It is a kind of triterpenoid extracted from the root of a traditional Chinese medicine called Tripterygium wilfordii . It was reported that celastrol could inhibit the development of IBD or colitis through several pathways, including: (1) regulating the oxidative stress and reducing lipid peroxide; (2) inhibiting the activation of the NLRP3 inflammasome; (3) increasing the levels of anti-inflammatory cytokines like IL-10; (4) enhancing the stability of intestinal epithelial barrier (152); (5) inhibiting the receptor interacting-protein 3/mixed lineage kinase domain-like protein-mediated programed necrosis pathway (153); and (6) inhibiting the production of NF-κB and its related inflammatory cytokines (154). Furthermore, it has been proven that celastrol can enhance the level of autophagy through the inhibition of the PI3K/Akt/mTOR signaling pathway in the colon tissue, and meanwhile reduce the production of several pro-inflammatory cytokines thus attenuating the inflammatory reaction in colon in IL-10-deficient mice (155).…”
Section: Pharmacological Intervention Of Autophagy In the Treatment Omentioning
confidence: 99%
“…The present study demonstrated that treatment with Celastrol significantly promoted Wnt and β-catenin protein expression levels in GIOP mice. Lin et al (12) previously reported that Celastrol ameliorates ulcerative colitis-associated colorectal cancer through β-catenin expression. The findings of the present study are consistent with previous finding (12) regarding the role of Celastrol as an effective activator of the Wnt/β-catenin pathway in GIOP mice and has a protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…1) has anti-oxidative and anti-inflammatory properties, inhibits atherosclerosis by lipoprotein oxidative modification and prevents against inflammation (11). Previous studies have revealed that Celastrol has anti-inflammatory, anti-bacterial, anti-viral, anti-fertility and insect-resistance functions, and has been used for the treatment of rheumatism, rheumatoid arthritis, blood diseases, skin diseases and as an agricultural insecticide (11,12). In the present study, bioinformatics analysis was used to investigate the effects of Celastrol on glucocorticoid-induced osteoporosis (GIOP) and the potential underlying molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Ayrıca; celastrolün hücre proliferasyonunu, apoptozu, proteazom aktivitesini,anjiyogenezi, ısı şok protein yanıtını ve adaptif immün yanıtı düzenlediği de bildirilmiştir. [15][16][17][18][19][20][21]…”
Section: Celastrolün Bi̇yoloji̇k Potansi̇yelleri̇unclassified